2008
DOI: 10.3892/ijo.33.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the mitochondria-driven pathway of apoptosis in human PC-3 prostate cancer cells by a novel hydrophilic paclitaxel derivative, 7-xylosyl-10-deacetylpaclitaxel

Abstract: Paclitaxel, a natural product originally isolated from Taxus brevifolia, belongs to the most successful anticancer drugs. Nevertheless, its poor water solubility represents a considerable disadvantage in clinical use, and novel derivatives with improved pharmacological features are required. We isolated 7-xylosyl-10-deacetylpaclitaxel from Taxus chinensis, which reveals higher water solubility than paclitaxel. This compound induced mitotic cell cycle arrest and apoptosis as measured by flow cytometry, DNA ladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…However when the two agents are combined, the loss of MMP is increased to 90% indicating that the combination is more effective in disrupting MMP. It has been demonstrated that activation of mitochondria driven pathway is a potential mechanism for induction of apoptosis by several compounds including dichloroacetate, sodium selenite and paclitaxel derivative in prostate cancer cells [35][36][37]. Our results showing induction of apoptosis through modulation of MMP is consistent with these observations.…”
Section: Involvement Of Bcl-2 In 2-me 2 Plus Eugenol Induced Loss Of Mmpsupporting
confidence: 95%
“…However when the two agents are combined, the loss of MMP is increased to 90% indicating that the combination is more effective in disrupting MMP. It has been demonstrated that activation of mitochondria driven pathway is a potential mechanism for induction of apoptosis by several compounds including dichloroacetate, sodium selenite and paclitaxel derivative in prostate cancer cells [35][36][37]. Our results showing induction of apoptosis through modulation of MMP is consistent with these observations.…”
Section: Involvement Of Bcl-2 In 2-me 2 Plus Eugenol Induced Loss Of Mmpsupporting
confidence: 95%
“…Cell viability (%) was calculated by [(experimental absorbance À background absorbance)/(control absorbance À background absorbance)] Â 100. Cell viability at different concentrations of compounds was plotted and 50% inhibition of growth was calculated as IC 50 (Jiang et al, 2008).…”
Section: In Vitro Assay For Antitumor Activitymentioning
confidence: 99%
“…The genus Taxus has been studied extensively for its taxoid compounds, particularly paclitaxel and its precursor 10‐deacetyl baccatin‐III. Many taxoids with antineoplastic, cytotoxic or antipromastigote activities have been isolated and investigated from the different organs of the Taxus genus (Chattopadhyay et al ., ; Dai et al ., ; Georgopoulou et al ., ; Jiang et al ., ).…”
Section: Discussionmentioning
confidence: 97%